Implementasi Komunikasi Profetik dalam Membangun Kesadaran Lingkungan di Kalangan Siswa SMK Bina Bangsa - Dwi Pratama, Eki (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2018)
Environmental awareness is a crucial aspect in building a society that cares about ecosystem sustainability. This study aims to explore the implementation of prophetic communication in fostering environmental awareness among students of SMK Bina Bangsa. The research method used is qualitative with a case study approach. The findings indicate that prophetic communication, based on transcendental, humanistic, and liberative values, successfully enhances students' understanding and behavior in protecting the environment. These findings contribute to the development of value-based educational strategies for environmental sustainability Keywords: Prophetic Communication, Environmental Awareness, Value-Based Education